OCCASIONAL TRANSFORMATIONS OF PROVERBIAL PHRASEOLOGISMS IN ENGLISH AND UZBEK LITERARY TEXTS (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2026)
This paper examines the occasional transformations of proverbial phraseologisms in English and Uzbek literary texts from a comparative linguistic perspective. In contemporary linguistics, proverbial phraseologisms are no longer regarded as fixed or “frozen” units of language; instead, they are viewed as dynamic and flexible expressions that may undergo semantic and structural modification in a specific literary context. The study situates proverbial phraseologisms at the intersection of phraseology and paremiology, highlighting their cultural, cognitive, and stylistic value.The research identifies the principal mechanisms of occasional transformation, including extension, ellipsis, substitution, contamination, and convergence, and analyzes their functions in selected works of English literature (Amy Tan, Jack London, Theodore Dreiser) and Uzbek literature (Abdulla Qahhor, Shuhrat). The findings demonstrate that, despite differences in cultural imagery and national mentality, both languages employ similar transformation strategies, with extension emerging as the most productive method. Occasional transformations do not distort traditional proverbs; rather, they revitalize collective folk wisdom and adapt it to modern social realities and individual artistic expression.